2004
DOI: 10.5194/angeo-22-2877-2004
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the ionospheric resonance cavity by neutral winds at middle latitudes

Abstract: Abstract.A new mechanism for the ionospheric Alfvén resonator (IAR) excitation at middle latitudes is considered. It is shown that the ionosphere wind system in this region is capable of sustaining the generation of geomagnetic perturbations that can be detected by ground magnetometers. The general IAR dispersion relation describing the linear coupling of the shear Alfvén and fast magnetosonic/compressional modes is obtained. The dependence of the IAR eigenfrequencies and damping rates on the perpendicular wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 23 publications
4
40
0
6
Order By: Relevance
“…As a possible source of the IAR excitation, the generation of the ionospheric turbulence and currents by the neutral wind in the lower ionosphere has been suggested (Surkov et al, 2004). These authors showed theoretically that a part of the neutral gas kinetic energy can be transferred into the energy of the electric current in the conductive ionosphere, which is then converted into the energy of Alfven and fast compressional MHD modes.…”
Section: Introductionmentioning
confidence: 99%
“…As a possible source of the IAR excitation, the generation of the ionospheric turbulence and currents by the neutral wind in the lower ionosphere has been suggested (Surkov et al, 2004). These authors showed theoretically that a part of the neutral gas kinetic energy can be transferred into the energy of the electric current in the conductive ionosphere, which is then converted into the energy of Alfven and fast compressional MHD modes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to find the electromagnetic perturbations in the atmosphere, we apply a Fourier transform to Equation (5). The results are given by b A − k 2 b A = 0 and e A − k 2 e A = 0.…”
Section: Basic Equationsmentioning
confidence: 99%
“…Similar mechanisms, i.e., the generation of GMPs, can be responsible for naturally occurring co-seismic electromagnetic effects associated with seismic wave propagation in solid geological media having conductivity, for example, in porous watersaturated rocks [3]. At the ionospheric D-and E-layer altitudes, the neutral winds and acoustic gravity waves give rise to entrainment of the ionospheric plasma particles with neutral molecules thereby exciting ionospheric currents and GMPs [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of the IAR excitation by the fluctuations of neutral gas velocity at the heights of the ionospheric E-layer was theoretically predicted by Molchanov et al (2004), and Surkov et al (2004). Fluctuations of the neutral particle velocity result in the alternating ionospheric current, which radiates MHD waves into the upper ionosphere.…”
mentioning
confidence: 99%